Palateless Overdenture: A Case Report - Prakyath, Malli; Vinaya, Bhat; Tripthi, Shetty (Journal of Health and Allied Sciences NU, 2017)
Palateless tooth supported overdenture is a treatment modality for patients to increase comfort as it aids in good retention, enhanced stability, better chewing efficiency and decreased alveolar bone resorption. This case report gives an insight into the step wise fabrication of a tooth supported palateless overdenture rather for better comfort, temperature and taste perception which is not possible as in case of a conventional complete denture.
Keywords: Palateless over dentures; Telescopi cover dentures; Gagging